2006
DOI: 10.1080/09603120600641375
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in Pakistani wood workers

Abstract: The lung function impairment is the most common respiratory problem in industrial plants and their vicinity. Therefore, the purpose was to study the affects of wood dust and its duration of exposure on lung function. This was a matched cross-sectional study of Spirometry in 46 non-smoking wood workers with age range 20 - 60 years, who worked without the benefit of wood dust control ventilation or respiratory protective devices. Pulmonary function test was performed by using an electronic Spirometer. Significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
5
17
0
2
Order By: Relevance
“…It was found in the study that mean FEV 1 and FVC values of the furniture workers were significantly lower than those of the control group; however, FEV 1 /FVC values were higher. In their studies Meo et al [29] and Milanowski et al [19] found decreases in FEV 1 and FVC of the workers exposed to wood dust compared with the control group. Mandryk et al [30] found lower FEV 1, FVC and FEF values for sawmill workers in their study.…”
Section: O R I G I N a L P A P E R S Ijomeh 2009;22(1) 47mentioning
confidence: 99%
“…It was found in the study that mean FEV 1 and FVC values of the furniture workers were significantly lower than those of the control group; however, FEV 1 /FVC values were higher. In their studies Meo et al [29] and Milanowski et al [19] found decreases in FEV 1 and FVC of the workers exposed to wood dust compared with the control group. Mandryk et al [30] found lower FEV 1, FVC and FEF values for sawmill workers in their study.…”
Section: O R I G I N a L P A P E R S Ijomeh 2009;22(1) 47mentioning
confidence: 99%
“…The worldwide community, especially the people in developing countries, is facing increasing risks of respiratory diseases due to production of smoke and dust in different occupational and industrial sectors [1,2]. The health risks posed by inhaled dust particles are influenced by the duration of exposure and the biological responses exerted by the particles [3].…”
Section: Introductionmentioning
confidence: 99%
“…Lung function impairment is the most common occupational respiratory problem in subjects exposed to dust in industrial sectors [2]. Studies are available on lung function and cement dust, but most of these studies were conducted without considering the long term duration-response effect between years of exposure and respiratory function impairment [7] and were not explained by promising physiological factors which greatly influence the lung function such as age, height, weight, ethnicity, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, KMC workers were excluded from the study. The reason for exclusion of a few different candidates was that they were already exposed to pollutants in cement [14], welding [15] and wood [16] industries that might impair lung function. Some other candidates refused to participate in the present study because they were afraid they could be forced to retire from their current jobs if their lung functions were found to be impaired.…”
Section: Subjectsmentioning
confidence: 99%